GROWTH OF Litopenaeus schmitti (BURKENROAD, 1936) AND Farfantepenaeus paulensis (PEREZ-FARFANTE, 1967) SHRIMP REARED IN RECIRCULATION CULTURE SYSTEM - Marcelo Barbosa Henriques; Pedro Mestre Ferreira Alves; Oscar José Sallée Barreto; Marcelo Ricardo de Souza (Brazilian Journal of Oceanography, 2014)
The Litopenaeus schmitti and Farfantepenaeus paulensis shrimp captured in estuaries are marketed as live bait for recreational fishing. As an alternative to shrimp extractive activities, the authors evaluated the rearing of these species in a recirculation culture system. For each species, the grow-out study was carried out in two 120-day production cycles, using 3,300 juveniles of an average length of 25 mm and weight of 0.9 grams in each, distributed in 12 tanks of 1,500 liters and 1.32 m2, at a population density of 208.3 shrimp per m2. The growth parameters were obtained using the von Bertalanffy model based on the length (mm) and age (weeks) data. The adjustments were made in the R environment of the non-linear least-square method. The von Bertalanffy growth model showed a proper fit, with determination coefficients of 0.900 for L. schmitti and 0.841 for F. paulensis. The values of L∞ and k were 172.66 and 0.027 mm for L. schmitti and 110.13 mm and 0.050 for F. paulensis, respectively. In the current study, L. schmitti showed negative allometric growth (p=4,314x10-18) and F. paulensis isometric growth (p=0.267). The growth of shrimp obtained in the proposed recirculation system can supply live bait for the sport fishing market.